Local Government Units' Access to the Private Capital Markets - Gilberto M. Llanto; Rosario G. Manasan; Mario B. Lamberte; Jaime C. Laya (Philippine Institute for Development Studies (PIDS), 1996)
The devolution of functions and responsibilities to LGUs has translated to the expectations of an improved delivery of public goods and services. However, LGU funding, mainly coming from the national government, loans from the government-owned financial institutions and Municipal Development Fund, have not been sufficient to meet the LGU requirement. This study provides results and analyses that can assist the government in developing a policy and institutional framework for the establishment of a municipal credit system well participated by the private sector.
Keywords: 330; capital markets; local government unit expenditures; Local Government Units (LGUs)